Molecular identification and localization of Trp homologues, putative calcium channels, in pregnant human uterus - Dalrymple, A; Slater, D M; Beech, D; Poston, L; Tribe, R M (Molecular human reproduction, 2002)
The mechanisms underlying the switch from uterine quiescence to contractile activity in labour are not clearly understood. Increasing evidence suggests that pathways of myometrial calcium homeostasis, including store-operated calcium entry (SOCE), may play an important role. The molecular basis of the membrane-associated calcium channels contributing to SOCE in pregnant human myometrium is not known, but they are likely to be hetero- or homo-oligomeric assemblies of transient receptor potential channel (TrpC) proteins, encoded by the mammalian homologues of Drosophila Trp genes. This study has therefore determined Trp gene expression and also TrpC protein expression and localization in term pregnant human myometrial tissue and primary cultured human myometrial smooth muscle (HMSM) cells. RT-PCR amplified fragments of Trp1, Trp3, Trp4, Trp6 and Trp7. PCR products were 100% homologous to published human sequences. Western blot analysis detected TrpC1, TrpC3, TrpC4 and TrpC6 proteins, which were of expected size. Immunolocalization revealed TrpC1, TrpC3, TrpC4 and TrpC6 protein expression in myometrial tissue and HMSM cells. TrpC protein immunostaining in HMSM cells was distributed in a distinct reticular fashion. TrpC proteins may be candidate proteins forming SOCE channels in term pregnant human myometrium.